77.4k views
1 vote
Kira is solving the equation 3(2x + 5) - (5x - 2) = 42. Her steps are shown below.

Step 1: 6x + 15 - (5x - 2) = 42
Step 2: 6x + 15 - 5x - 2 = 42
Step 3: x + 15 – 2 = 42
Step 4: x + 13 = 42
ď
D) 2.
In which step does a mistake first appear?
D.
CLEAR AL
help ?

User Nbonbon
by
5.2k points

2 Answers

3 votes

Answer:

D) 2

Explanation:

User RomanistHere
by
5.9k points
2 votes

Answer:

D)2

the minus sign outside the bracket when multiplied by a negative number in the bracket is equal to a positive number

User Tughi
by
5.6k points